EBSCOhost - Buys, Matthew (My University, 2012)
Education is a central socio-economic right that provides the foundation for life-long learning and economic opportunities. Literacy data published by the UNESCO1 Institute for Statistics (UIS) in 2007 shows that the lowest adult literacy rates are observed in Africa and South Asia. In some countries, fewer than three out of ten adults can read and write. UIS provides national literacy data for two age groups: youths aged 15 to 24 years, and adults aged 15 years and older.
Keywords: EBSCOhost